Static analysis and optimization design of a small grass-grid laying device - Sheng, Jing; Chen, Yongwei; Liu, Guoman; Deng, Shunhu; Xu, Hao (International Journal of Agricultural and Biological Engineering, 2026)
With the growing global focus on environmental protection, desertification control has attracted widespread attention. Traditional manual straw checkerboard sand barrier laying is limited by low efficiency and high labor costs. This study presents the development of a compact straw checkerboard laying device to replace manual operation and achieve efficient, low-cost desertification control. Mathematical analysis, Matlab-based parameter optimization, and finite element analysis (FEA) were performed to support the lightweight design of the device frame and core straw-pressing roller. A scaled demonstration prototype was fabricated, and comparative tests were conducted to verify the optimization effect. The optimized straw-pressing roller achieved a 17.87% weight reduction with nearly unchanged mechanical properties, with performance fully meeting the material strength requirements. Comparative tests confirmed no significant difference in working performance between the pre- and post-optimized rollers. This device satisfies the standard requirements of straw checkerboard laying, providing a technical reference for the development of lightweight sand fixation equipment. Key words: small grass-grid laying device; grass-pressing wheel; desert control; optimal analysis; static analysis DOI: 10.25165/j.ijabe.20261904.9737 Citation: Sheng J, Chen Y W, Liu G M, Deng S H, Xu H. Static analysis and optimization design of a small grass-grid layingdevice. Int J Agric & Biol Eng, 2026; 19(4): 133–142.